The effect of delivery speed a nd trust on ewom through repurchase intentions at Shopee Express in Sidoarjo - Ach Jainur Reo Fajar; Muhafidhah Novie (Institute of Computer Science (IOCS), 2024)
This study aims to determine the effect of delivery speed and trust on e-wom through repurchase interest in shopee express in Sidoarjo. The research method used is quantitative with a descriptive approach. The number of samples in this study were 100 respondents, and the data were collected through the use of questionnaires. Data analysis was carried out using the path analysis methsod, while the sampling technique used was non probability sampling. The results showed that 1) Delivery Speed has a positive but insignificant influence on E-Wom. 2) Delivery Speed has a positive and significant influence on Repurchase Intention. 3)Trust has a positive and significant influence on Ewom. 4) Trust has a positive but insignificant influence on Repurchase Intention. 5) E-Wom has a positive and significant influence on Repurchase Intention